Kata Panggilan Masyarakat Kelabit - Sawan @ Mohammad Syawal, Narawi (2012)
This study on terms of address practice is pursued based on current scenario, and issues related to terms of address practices within the Kelabit ethnic community. The aim of this qualitative case study is to explain the use of address within the Kelabit society and the challenges in sustaining its usage in tandem with globalization. The objectives of this research are as follows: (1) to analyze and to ascertain the structure, category, meaning and usage of terms of address within the Kelabit community; (2) to explain the etiquette in the usage and practice of terms of address within the Kelabit community; and (3) to elicit the challenges on the practice and usage of terms of address within the Kelabit community. This research is conducted at Bario Highlands, Miri and Bintulu, Sarawak. Eleven Kelabit ethnic representatives from Bario Highlands ages between 40 and 70 participated as the study informants between 2006 to 2010. The study used interview as its primary data gathering tool, and complimented by study observation and document analysis. This study employed Harimurti Kridalaksana Theory (1983), Ervin-Tripp Theory (1976) and Relevance Theory by Sperber and Wilson (1986). This study can be concluded that: the usage of terms of address is closely related to Kelabit socio culture which is determined by age variable, context and the interlocutors. The correct usage of terms of address in Kelabit portrays courtesy and politeness in addressing and finally, it was also found that the usage of terms of address within the urban area evidently showing some changes and is influenced by language and foreign culture.